Literature: A Realistic Representation of Life - Bhat, Intikhab Alam (Innovative Research Thoughts, 2017)
The word ‘Literature’ evokes various ideas and encompasses different forms, styles and motives. The prominent dictionaries claim it to be, ‘writing in prose or verse, especially: writings having excellence of form or expression and expressing ideas of permanent or universal interest.’ History bears witness of the phenomenal changes and revolutions which literary works and words or in short, literature have brought upon the human civilization. So can it be considered that literature is a realistic representation of life? “For literature as a whole grows and changes from generation to generation.... A writer of exceptionally powerful personality is certain to stamp his impress upon his age.”[1] The purpose of this research paper is to explore the realistic approach of literature and how it invokes the real and sometimes bitter realities of our world. While sometimes create hope and assurance of a better future. Sometimes becomes the mouth piece of the subjugated and victimised, while sometimes it becomes a weapon to instigate insult and guilt in the mind of the oppressor. Literature can be a medium of appraisal, and equally, it can be a medium of criticism. This multi dimensional and multi faced environment that is woven around literature is to be explored in this paper.